Stating the Family : New Directions in the Study of American Politics - Nackenoff, Carol; Novkov, Julie, 1966- (Book collections on Project MUSE., 2020)
"The family has become a nodal point for the political disputes and social divisions that characterize the nation today, including matters such as marriage, gender identity, immigration reform, and welfare programs. The family is frequently discussed in party platforms and by political nominees, often marking the gulf between liberal and conservative. Despite the key role it plays in politics, public policy, and American political development, the family has not received the attention it is due by political scientists-especially privileged male scholars-who have largely disregarded the topic as belonging to a supposedly nonpolitical state of nature or "private sphere." More recently, however, theorists have explored the way the family affects the state and the state in turn affects, even constitutes, families. Family does not exist in a protected state of nature separate from the political, but instead both family and state determine each other. Extending this line of inquiry, the contributors to Stating the Family examine the role of family in American political development, particularly in the context of the rise of neoliberalism. While the family has been relied upon as the silent institutional partner of the state, neoliberal policies of privatization have undercut support for the family, which in turn has significant implications for the state. The contributors to Stating the Family cover such topics as marriage equality, interracial unions, birthright citizenship, immigration policy, and the role of the family in the political inclusion of women. Though the family has long been an invisible force within American political development, the essays in this volume help make visible the place of this important institution in the law, regulation, and policy of the American state"--